Pengaruh Lingkungan Keluarga terhadap Pembentukan Karakter Peserta Didik - Rahayu, Fanny Septiany (Indonesian Journal of Educational Counseling, 2024)
This research aims to see the extent of the influence of the family environment on the formation of student character. The family is the first and main educational environment for children. The birth of the family as an educational institution since humans were still in the womb and then existed in the world. The duties and responsibilities of parents in the family environment are to lay the foundation of moral values ​​for the formation and development of children in the future, so that children can grow and develop well because it is in the family environment that children first receive the basic knowledge about values. kind. The research method used in this research is a descriptive method with a quantitative survey approach. The results of this research show that the regression coefficient value for the family environment variable is 0.753 or 75.3%, so it can be said that the family environment has an influence on the formation of student character at SD Negeri 2 Arjawinangun by 75.3%. This shows that the family environment has a big influence on the formation of students' character, while the remaining 24.7% of students' character formation is influenced by other factors.